Pariška leta Antona Ocvirka - Smolej, Tone (Primerjalna književnost, 2005)
The article explores the time (1931/32 and 1932/33) that Anton Ocvirk, later the founder of comparative literary science in Slovenia, spent as a post-graduate student in Paris. It begins by portraying Ocvirk's connections with French writers and Russian intellectuals, also through some previously unpublished correspondence, and then focuses on his studies at the College de France under Paul Hazard.
Keywords: Ocvirk, Anton, 1907-1980; slovenska literarna veda; literarni zgodovinarji; literary historian; biografije